Manajemen risiko perbankan syariah dalam menghadapi disrupsi teknologi pada era digitalisasi - Farichah, Miftahul (Maliki Interdisciplinary Journal, 2025)
The rapid development of digital technology has brought significant changes in the banking sector, including Islamic banking. Technological disruption not only creates opportunities, but also raises various risks that require adaptive and strategic managerial responses. This research aims to analyze the risk management implemented by Islamic banking in facing the challenges of technological disruption in the digitalization era. This study uses a qualitative method with a descriptive approach. The data collection technique in this study is to use secondary data sources through literature reviews and previous research sources. The results of the study show that Islamic banks implement risk management through four main stages: identification, measurement, monitoring, and risk control. This strategy includes regular audits, strengthening the digital security system, involving the Sharia Supervisory Board, as well as implementing technology that is in accordance with Islamic values ​​such as the prohibition of usury, gharar and maysir, as well as a commitment to Maqasid al-Syariah.